Experimental rig investigation of a direct interconnection technique for airborne wind energy systems. (December 2020) - Salari, Mahdi Ebrahimi; Coleman, Joseph; O'Donnell, Cathal; Toal, Daniel
Highlights: The first practical study on direct interconnection of airborne wind generators (AWE). Development of a scaled hardware setup emulating pumping mode AWE's power take-off. Design and test of a comprehensive direct interconnection system for an AWE farm. Abstract: Airborne wind energy is a new approach to reach the stronger and more consistent winds at higher altitudes. In this paper, the interconnection of pumping mode airborne wind energy systems inside an energy farm is investigated. An experimental rig hardware setup has been designed and built to model an AWE farm in small scale. A direct interconnection system has been developed and examined on the experimental test rig. The direct interconnection technique (DIT) is a new method developed for the interconnection of marine wind energy systems within an energy farm, without requiring offshore-based power electronic converters. DIT relocates power electronic converters from the offshore site to the shore substation by interconnecting marine generators directly to a common bus. This method makes possible significant improvements to the economy and reliability of marine renewable energy systems. In this paper, for the first time, the direct interconnection technique is investigated experimentally for physically emulated pumping mode airborne wind energy systems. The construction of the experimental rig hardware setup is described, and the laboratory test results for the direct interconnection of airborne wind energy systems are presented and discussed.